Along-slope bottom currents driven by dissipation of internal tides in the northeastern South China Sea - Wang, Jiannan; Xie, Xiaohui; Li, Shaofeng; Zhang, Han; Li, Wei (Frontiers in Marine Science, 2023)
Recent mooring observations on the continental slope on the east side of the Dongsha Island in the northeastern South China Sea (SCS) showed that an along-slope bottom current can be generated when internal tides obliquely incident to the slope are dissipated near the seafloor. In this study, new mooring data collected on the south side of the Dongsha Island are used to explore the universality of internal wave driven the bottom currents and test the ability of the previous theory in estimating the along-slope current. The data show strong near-bottom energy dissipation due to the critical reflection of diurnal internal tides on the continental slope, with a time-mean depth-integrated dissipation rate of ~4.8×10-3 W/m2. Because of the obliquely incident of diurnal internal tides to the slope, near-bottom dissipation of internal tides generates a southwestward along-slope current, with the maximum velocity exceeding 6 cm/s. By comparing the observations, the previous theory for internal wave induced mean flows developed by Thorpe (1999) shows a good ability to estimate the along-slope bottom current velocity. Based on the theory, as well as modelled energy dissipation on the entire continental slope in the northeastern SCS, a map is obtained to quantitatively describe the along-slope bottom flow caused by internal tide breaking on the slope.